NOTES ON HUMAN- HYENA (Hyaena hyaena, Linnaeus 1751) CONFLICT IN JAJARKOT, KALIKOT AND MAHOTTARI DISTRICTS OF NEPAL (Journal of Institute of Science and Technology, 2017)
Striped hyena is one of the large carnivores of the forest and grassland ecosystem. This paper deals with the distribution and human hyena conflict status in Jajarkot, Kalikot, and Mahottari districts of Nepal. Questionnaire and sign survey methods were used to collect information on human-hyena conflict. This study indicated that human hyena conflict was high in the selected district. Eight striped hyenas died in between 2015-2016 due to the human-hyena conflict. Livestock depredation by striped hyena was one of the major reasons of the human-hyena conflicts in Nepal. The goat was the most preyed species by the striped hyena. This study shows that the distribution of striped hyena was recorded from lowland to mid hills region of Nepal. The conservation outreach programs should be formulated to conserve the habitat and maintain the prey population of the striped hyena which would be helpful for long term conservation of the striped hyena in Nepal.Journal of Institute of Science and TechnologyVolume 22, Issue 1, July 2017, Page: 127-131